Usulan Pengendalian Kualitas Produksi Benang Carded dengan Metode Six Sigma - Manan, Abdul; Handika, Firdanis Setyaning; Nalhadi, Ahmad (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2018)
A yarn company strives to produce good and quality products, but the production process that is carried out by each person will produce products targeted at a target that has been set at 5%. This study uses the Six Sigma method but only until the improvement stage. The research is to determine the DPMO value and sigma level in the spinning production process, to know what factors cause defects and new parameters to reduce the defect. Based on the results of the study that the DPMO on the type of CD thread in the spinning section is 17,130 and the sigma level is 3,6. The level of sigma that has dominated the Indonesian industry average, but has a defect of 8.7%, the target set at 5%. Damaged and dirty apron, clogged trumpet, and leaky hose are factors that plan defects. Furthermore, with Failure Mode Effect Analysis (FMEA), the highest value of Risk Priority Number (RPN) in tangled defects is that the apron is damaged (140) and clogged trumpet (120), while the highest RPN value is gross dirty, i.e., dirty apron (150) and hose leaking lubricant (120).